Operational Risk and Financial Performance of Banks in The Middle East and North Africa - Yousef, Amer N. Bani; Taha, Roshaiza; Muhmad, Siti Nurain; Zainul Abidin, Ahmad Firdhauz (Universiti Utara Malaysia Press, 2023)
This study examines the relationship between operational risk and financial performance of banks in the Middle East and North Africa (MENA), utilising data from 135 banks spanning 14 countries from 2015 to 2019. The results show that operational risk negatively affects banks’ financial performance in the MENA region. This study recommends that banks tailor and constantly improve their risk management process to put operational risk management and control processes in place. The findings entail the importance of developing relevant frameworks and policies for prompt action in reporting and recording operational loss. Thus, banks’ management should formulate and implement appropriate procedures to ensure that timely information is obtained, especially regarding profit and loss, which will ultimately help boost the banks’ financial performance in the MENA region. This study is unique as it contributes to the existing body of knowledge by investigating the role of operational risk in determining banks’ financial performance in the MENA region.